Improvement in protein separation by pH excursion modulated ion-exchange chromatography - Raja Ghosh (Journal of Chromatography Open)
The transient change in pH during the elution step in ion exchange chromatography is commonly referred to as pH excursion. Acidic pH excursion is usually observed during salt-based elution in cation exchange chromatography. This could have a detrimental effect on protein stability as well as on protein separation. Acidic pH excursion could delay protein elution and thereby decrease resolution of sequentially eluted proteins. In a recent study, a method for suppressing or modulating pH excursion has been discussed. In the current study, the feasibility of using this approach for increasing resolution in protein separation is examined. Modulation of pH excursion during elution resulted in the rapid release of a weakly bound protein from cation exchange media while the release of a strongly bound protein remained largely unaffected. This differential effect was utilized to increase the resolution in binary protein separation. The resolution obtained in pH excursion modulated cation exchange chromatography was significantly greater than that obtained with unmodulated (or control) cation exchange chromatography, i.e., where acidic pH excursion was allowed to happen as usual. This approach for increasing resolution in protein separation could potentially be utilized in different analytical and preparative protein chromatography applications.